Ilusi Fiskal dan Flypaper Effect pada Belanja Daerah Kabupaten/Kota di Sulawesi Selatan - Magfirah Wahyu Ramadhani; Dwi Utami; Ambarwati Akib (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to examine how fiscal illusion and the flypaper effect are reflected in transfer-based local expenditure planning among regency and municipal governments in South Sulawesi. The study employed a qualitative descriptive approach using document analysis of Regional Government Work Plans, General Budget Policies and Provisional Budget Ceiling Priorities, Regional Budgets, Budget Realization Reports, local government performance reports, and fiscal data from official government sources during 2020–2024. Data were analyzed using qualitative content analysis and thematic analysis. The findings indicate that central government transfers function as the primary fiscal reference in determining expenditure priorities, sustaining operational spending, and supporting mandatory public service obligations. The study also reveals weak integration between local own-source revenue strategies and expenditure restructuring, indicating the presence of fiscal illusion in budget narratives. These findings imply the importance of integrating local revenue strategies, expenditure prioritization, and fiscal sustainability to strengthen local fiscal independence.